Potentiation of Brain-Derived Neurotrophic Factor-Induced Protection of Spiral Ganglion Neurons by C3 Exoenzyme/Rho Inhibitor - Jennifer Harre; Jennifer Harre; Laura Heinkele; Melanie Steffens; Athanasia Warnecke; Athanasia Warnecke; Thomas Lenarz; Thomas Lenarz; Ingo Just; Astrid Rohrbeck (Frontiers in Cellular Neuroscience, 2021)
Preservation of the excitability of spiral ganglion neurons (SGN) may contribute to an improved speech perception after cochlear implantation. Thus, the application of exogenous neurotrophic factors such as the neurotrophin brain-derived neurotrophic factor (BDNF) to increase SGN survival in vitro and in vivo is a promising pharmacological approach in cochlear implant (CI) research. Due to the difficult pharmacokinetic profile of proteins such as BDNF, there is a quest for small molecules to mediate the survival of SGN or to increase the efficacy of BDNF. The C3 exoenzyme from Clostridium botulinum could be a potential new candidate for the protection and regeneration of SGN. Inhibition of the RhoA GTPase pathway which can be mediated by C3 is described as a promising strategy to enhance axonal regeneration and to exert pro-survival signals in neurons. Nanomolar concentrations of C3, its enzymatically inactive form C3E174Q, and a 26mer C-terminal peptide fragment covering amino acid 156–181 (C3156-181) potentiated the neuroprotective effect on SGN mediated by BDNF in vitro. The neuroprotective effect of C3/BDNF was reduced to the neuroprotective effect of BDNF alone after the treatment with wortmannin, an inhibitor of the phosphatidylinositol-3-kinase (PI3K).The exoenzyme C3 (wild-type and enzyme-deficient) and the C3 peptide fragment C3154–181 present novel biologically active compounds for the protection of the SGN. The exact underlying intracellular mechanisms that mediate the neuroprotective effect are not clarified yet, but the combination of BDNF (TrkB stimulation) and C3 exoenzyme (RhoA inhibition) can be used to protect SGN in vitro.